Serum albumin or body mass index: Which prognostic factor for survival in patients with acute myeloblastic leukaemia?. Issue 1 (5th October 2018) - Filliatre‐Clement, Lauriane; Broseus, Julien; Muller, Marc; Hosseini, Kossar; Rotonda, Christine; Schirmer, Luciane; Roth‐Guepin, Gabrielle; Bonmati, Caroline; Feugier, Pierre; Béné, Marie‐Christine; Perrot, Aurore
Abstract: Obesity has been associated with an increased risk of developing acute myeloblastic leukaemia (AML). The outcome of AML patients could thus be dependent on their nutritional status that can be evaluated by the simple measurement of serum albumin (SA) and body mass index (BMI). These two parameters could have a value as prognostic factors to guide patients' management. We evaluated the association between SA levels, BMI, and survival, evaluated as overall survival (OS) and event‐free survival. Furthermore, we investigated the association between BMI, SA, and other prognostic factors of interest in AML. This retrospective single‐center study included 159 patients diagnosed with AML at Nancy Hospital between 2005 and 2013, treated with aracytine and anthracycline. Forty‐four percent of patients presented with normal weight while 56% were obese/overweight. Serum albumin levels were <30 g/L for 49 patients, and ≥30 g/L for 110. Thirty‐four patients with low SA levels were also obese. Favourable OS was associated with SA levels ≥30 g/L (HR = 0.467; 95% CI 0.230‐0.946; P = .034) but was not impacted by the BMI. Serum albumin levels appear to be an independent prognostic factor in AML and a better parameter than BMI for evaluating the nutritional status of patients at diagnosis.